Inequalities in global health: a world-system analysis, 1945-present - Collins, Anna L. (Kansas State University, 2013)
World-system theorist Immanuel Wallerstein made two theoretical assertions in Historical Capitalism that (a) significant inequalities in the “margin of safety against…endemic dangers and erratic violence” for people in different zones of the world economy persisted over long periods of time and (b) that the “margin of safety” for people in the periphery has actually deteriorated. This study set out to test this theory by examining mortality data for countries in different zones of the world-economy. It identified a set of health-related proxies for “endemic dangers and erratic violence”, infectious diseases (malaria, polio, tuberculosis, and influenza), chronic diseases (cancer, diabetes, and cardiovascular), erratic violence (homicide, suicide, and motor vehicle accidents), and also infant mortality and life expectancy for women and men. It gathered data from the United Nations Statistical Division’s Demographic Yearbook for a select sample of countries in different zones of the world-economy (core, semiperiphery, and periphery) from 1950 to 2010, and examined how mortality from these dangers changed during this period. This study found that mortality data for infectious diseases did not provide much support for Wallerstein’s theoretical assertions. But the mortality data for chronic disease and erratic violence provided strong support for Wallerstein’s assertions. The data on life span provided some support for Wallerstein’s first assertion, but not for his second. Overall, the findings generally support Wallerstein’s theories and suggest ways that health-related inequalities might be addressed.
Keywords: Inequality; Globalization; Mortality; World-system; Wallerstein; Medicine (0564); Nursing (0569); Public Health (0573)